The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1534/g3.118.201012
|View full text |Cite
|
Sign up to set email alerts
|

Global Shifts in Gene Expression Profiles Accompanied with Environmental Changes in Cnidarian-Dinoflagellate Endosymbiosis

Abstract: Stable endosymbiotic relationships between cnidarian animals and dinoflagellate algae are vital for sustaining coral reef ecosystems. Recent studies have shown that elevated seawater temperatures can cause the collapse of their endosymbiosis, known as ‘bleaching’, and result in mass mortality. However, the molecular interplay between temperature responses and symbiotic states still remains unclear. To identify candidate genes relevant to the symbiotic stability, we performed transcriptomic analyses under multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…This transcriptional response is controlled in part by the transcription factor HSF1 (30,31,33), so that reducing HSF1 function can have dramatic effects on organismal heat tolerances (29,32). Given this background, it is not surprising that many studies in corals and other cnidarians have found induction of genes encoding HSPs and HSF1 during heat stress (23)(24)(25)(26)(27)46). Here, we have shown that ablation of HSF1 function in A. millepora by CRISPR/Cas9-induced mutations leads to rapid death of larvae under heat stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transcriptional response is controlled in part by the transcription factor HSF1 (30,31,33), so that reducing HSF1 function can have dramatic effects on organismal heat tolerances (29,32). Given this background, it is not surprising that many studies in corals and other cnidarians have found induction of genes encoding HSPs and HSF1 during heat stress (23)(24)(25)(26)(27)46). Here, we have shown that ablation of HSF1 function in A. millepora by CRISPR/Cas9-induced mutations leads to rapid death of larvae under heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the prominent role of thermal stress in the decline of corals worldwide, a major focus of research is to understand both (i) the mechanisms that lead to heat-induced bleaching and death and (ii) those that may protect against it. Studies in many organisms, including symbiotic corals and anemones, have found an extensive burst of transcription upon heat stress; the upregulated genes include many encoding molecular chaperones such as HSP70 and HSP90 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, for several reasons, it has remained unclear whether this transcriptional response has a role either in producing or in protecting against bleaching and death in corals and anemones.…”
mentioning
confidence: 99%
“…However, that study only examined gene expression during the first few hours of heat stress, so that the full dynamics of the NFκB response remained unclear. Moreover, another study that examined early time points did not note changes in NFκB mRNA levels (19), whereas of two studies that examined a later time point (∼24 h of heat stress), one reported elevated levels of NFκB mRNA (26) while the other did not (27). A sustained elevation of NFκB mRNA during heatinduced bleaching would be consistent with the evidence that NFκB protein is present at lower levels in symbiotic than in aposymbiotic animals, which may be necessary to avoid innateimmune rejection of the foreign cells (28).…”
Section: Significancementioning
confidence: 96%
“…A July 2019 study found that 292 cnidarian genes in transcriptome analysis of the symbiotic sea anemone Exaiptasia diaphana, a close relative and emerging model organism of corals, changed their expression levels at bleaching-threshold temperatures (12). Some of the most affected genes are involved in metabolizing sugars, which the algae normally provide to the coral.…”
Section: Forward Thinkingmentioning
confidence: 99%